2013
DOI: 10.1021/jp404580v
|View full text |Cite
|
Sign up to set email alerts
|

UV Photodissociation of Pyrroles: Symmetry and Substituent Effects

Abstract: H (Rydberg) atom photofragment translational spectroscopy and ab initio electronic structure calculations are used to explore ways in which ring substituents affect the photofragmentation dynamics of gas phase pyrroles. S 1 S 0 (*π) excitation in bare pyrrole is electric dipole forbidden, but gains transition probability by vibronic mixing with higher electronic states.The S 1 state is dissociative with respect to N-H bond extension, and the resulting pyrrolyl radicals are formed in a limited number of (non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
48
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(59 citation statements)
references
References 28 publications
11
48
0
Order By: Relevance
“…This is a direct result of DMP r being populated in only a limited set of vibrational states, predominately in v = 0. This result is in excellent agreement with the H Rydberg atom photofragment translational spectroscopy (HRA-PTS) studies of Karsili et al 14 Through consideration of the above energetics, we can determine the TKER for dissociation into DMP r and H atom photofragments according to the relationship…”
Section: Resultssupporting
confidence: 88%
“…This is a direct result of DMP r being populated in only a limited set of vibrational states, predominately in v = 0. This result is in excellent agreement with the H Rydberg atom photofragment translational spectroscopy (HRA-PTS) studies of Karsili et al 14 Through consideration of the above energetics, we can determine the TKER for dissociation into DMP r and H atom photofragments according to the relationship…”
Section: Resultssupporting
confidence: 88%
“…Since the ex-tremely low oscillator strength of the πσ * state seems to place the observation of its dynamics below the sensitivity of the applied experimental technique, the study of pyrrole methylated derivatives as 2-5dimethylpyrrole and N-methylpyrrole, which retaining the same relevant electronic structure, permits a more efficient photoexcitation 44,55,56 that could provide highly relevant dynamical data. Experiments on these species are being run in our lab at the present time.…”
Section: Discussionmentioning
confidence: 99%
“…Using photofragment translational spectroscopy (PTS), Blank et al found upon excitation at 193 and 248 nm that the H elimination channel is the main dissociation channel. 1 Later, higher energy-resolution experiments [4][5][6][7][8]15 in the wavelength range 193.3-254.0 nm observed two components in the H product translational energy distributions: a "fast" component with a higher, sharp kinetic energy distribution and a "slow" component with a lower, broad kinetic energy distribution. A picture was proposed as follows: upon the approach of the wavepacket to the conical intersection (CI) between the πσ * and ground states, the wavepacket either evolves to the ground state and results in a statistical dissociation of the hot ground state, leading to nascent H-atoms with lower kinetic energies, or evolves diabatically leading to a direct cleavage of the N-H bond to yield H-atoms with higher kinetic energies.…”
Section: Introductionmentioning
confidence: 99%